Patient‐hematologist discordance in perceived chance of cure in hematologic malignancies: A multicenter study. Issue 6 (6th December 2019) - Loh, Kah Poh; Xu, Huiwen; Back, Anthony; Duberstein, Paul R.; Gupta Mohile, Supriya; Epstein, Ronald; McHugh, Colin; Klepin, Heidi D.; Abel, Gregory; Lee, Stephanie J.; El‐Jawahri, Areej; LeBlanc, Thomas W.
Abstract : Background: Ensuring that patients with hematologic malignancies have an accurate understanding of their likelihood of cure is important for informed decision making. In a multicenter, longitudinal study, the authors examined discordance in patients' perception of their chance of cure versus that of their hematologists, whether patient‐hematologist discordance changed after a consultation with a hematologist, and factors associated with persistent discordance. Methods: Before and after consultation with a hematologist, patients were asked about their perceived chance of cure (options were <10%, 10%‐19%, and up to 90%‐100% in 10% increments, and "do not wish to answer"). Hematologists were asked the same question after consultation. Discordance was defined as a difference in response by 2 levels. The McNemar test was used to compare changes in patient‐hematologist prognostic discordance from before to after consultation. A generalized linear mixed model was used to examine associations between factors and postconsultation discordance, adjusting for clustering at the hematologist level. Results: A total of 209 patients and 46 hematologists from 4 sites were included in the current study. Before consultation, approximately 61% of dyads were discordant, which improved to 50% after consultation ( P  < .01). On multivariate analysis, lower educational level (<college vs postgraduate: odds ratio [OR], 2.24; 95% CI, 1.02‐4.92), higher social support–affection subscale score (1‐unit change in score: OR, 1.15; 95% CI, 1.00‐1.32), and discordance before consultation (OR, 6.17; 95% CI, 2.99‐12.72) were found to be significantly associated with discordance after consultation. Conclusions: Patient‐hematologist concordance in prognostic understanding appears to improve after a hematology consultation, but approximately one‐half of patients' views of their prognoses were found to remain discordant with those of their hematologists. Interventions are needed to improve prognostic understanding among patients with hematologic malignancies. Abstract : Patient‐hematologist discordance with regard to perceived chance of cure was found to occur in >60% of dyads in the current study, but decreased to 50% after a hematology consultation. There is a need for interventions to improve prognostic understanding among patients with hematologic malignancies.